Churg-Strauss syndrome with cardiac involvement: case illustration and contribution of CMR in the diagnosis and clinical follow-up. (1st May 2018) - d'Ersu, E.; Ribi, C.; Monney, P.; Vincenti, G.; Schwitter, J.; Rotman, S.; Hullin, R.; Regamey, J.
Abstract: This report summarises three cases of Churg-Strauss syndrome (CSS) illustrating the diagnostic challenges associated with the cardiac manifestation of this disease. Here, we illustrate the role of cardiac magnetic resonance (CMR) for diagnosis and follow-up of CSS with a focus on new non-contrast T2 -weighted imaging sequences for quantification of myocardial scar tissue and quantitative T2 mapping techniques, which allow the detection of myocardial edema. Highlights: Cardiac involvement in the rare Churg-Strauss syndrome is highly prevalent, but remains a diagnostic challenge. A multimodal and multidisciplinary approach is mandatory for the initial diagnosis. CMR and its new non-contrast sequences offer a non-invasive modality for the clinical follow-up under immunosupressive therapy.